1988
DOI: 10.1017/s095026880006725x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses of swine to type A influenza viruses during the past ten years in Japan

Abstract: SummaryA total of 6346 swine sera collected at an abattoir in the city of Obihiro, Hokkaido during the years 1978–87 were tested for the presence of antibodies to swine and human influenza viruses. A high incidence of antibody to A/New Jersey/8/76 (swine type H1N1) virus was observed throughout the 10 years except for the occasional month and a single long period of 15 months. Antibodies to human H3N2 virus in swine appeared to be related to the epidemics of human influenza which occurred in the study area dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Sera from positive animals reacted in HI tests with human HINI viruses predominantly with the prevailing strain in the human population (A/Taiwan/1/86). These findings are consistent with previous studies where antibodies in pigs to human HINI viruses were recognized in relation to HiN1 influenza epidemics in the human population [2,15,16,24]. These viruses apparently fail to persist in the pig population, although seropositive animals to a strain of human HiNt virus which had circulated 30 years earlier have been reported [25].…”
Section: Discussionsupporting
confidence: 91%
“…Sera from positive animals reacted in HI tests with human HINI viruses predominantly with the prevailing strain in the human population (A/Taiwan/1/86). These findings are consistent with previous studies where antibodies in pigs to human HINI viruses were recognized in relation to HiN1 influenza epidemics in the human population [2,15,16,24]. These viruses apparently fail to persist in the pig population, although seropositive animals to a strain of human HiNt virus which had circulated 30 years earlier have been reported [25].…”
Section: Discussionsupporting
confidence: 91%
“…Our previous reports also indicated that a number of pigs had detectable antibodies to swine H1N1 viruses throughout the observation period (Goto et al, 1988). The pigs were infected with human H1N1 or H3N2 virus during the human epidemics of each virus (Miwa & Goto, 1986).…”
mentioning
confidence: 88%
“…The H3N2 swine virus was apparently derived from humans. The appearance of H3N2 in swine subsequent to H3N2 human epidemics has been documented extensively (Chang et al, 1977;Goto et al, 1988;Tumova et al, 1976;Tumova et al, 1980a;Wallace, 1979;Wibberley et al, 1988). Interestingly, even after the A/Hong Kong/1/68 (H3N2) influenza virus was no longer circulating in the human population, it has been maintained in the swine populations (Shortridge et al, 1977;Tumova et al, 1980b).…”
Section: Swine Influenza Virusmentioning
confidence: 99%